DEVELOPMENT OF WORKSHEET BASED ON INQUIRI WITH SAINTIFIC APPROACH TO TRAIN STUDENT CRITICAL THINKING ON THERMOCHEMISTRY MATERIAL (Universitas Negeri Surabaya, 2018)
This study aims to train the students’ critical thinking based on inquiry with scientific approach on thermochemistry material. Assessment on worksheet is based on theoretical and empirical assessment, in which theoretical value according to Permrendikbud is material compatibility, presentation, language, graph. This study uses type of research of development method with Research & Development (R & D) model on a limited trial. This study is a quantitative method with Pretest Posttest Desaign. This study was conducted in SMAN 2 KOTA MOJOKERTO. Sources of data in this study are the review, validation and students’ response, pretest and posttest question sheets based on inquiri with scientific approach that tested on 16 students. The study was conducted three times. Percentage of validity on worksheet with presentation of each criterion are between 75% - 100%. Critical thinking skills are motivation, considering the credibility of information resources, inducing and considering induced results, observing and considering observations, categorized in very good order (90% - 80%), very good (100%), very good (86.67%-100%), and very good (100%). Students’ response on the developed of worksheet are reviewed theoretically and empirically from the content/material, linguistic presentation, and graph criteria, show a positive response in which the percentage obtained for each criterion are between 87.50%-100%, thus categorized as feasible source of learning . Keywords: Critical Thinking, Inquiry, Scientific